Process simulation of blue hydrogen production by upgraded sorption enhanced steam methane reforming (SE-SMR) processes - Yan, Yongliang; Thanganadar, Dhinesh; Clough, Peter T.; Mukherjee, Sanjay; Patchigolla, Kumar; Manovic, Vasilije; Anthony, Edward J. (Elsevier, 2020)
Clean and carbon-free hydrogen production is expected to play a vital role in future global energy transitions. In this work, six process arrangements for sorption enhanced steam methane reforming (SE-SMR) are proposed for blue H2 production: 1) SE-SMR with an air fired calciner, 2) SE-SMR with a Pressure Swing Adsorption (PSA) unit, 3) SE-SMR thermally coupled with Chemical-Looping Combustion (CLC), 4) SE-SMR+PSA+CLC, 5) SE-SMR+PSA with an oxy-fired calciner, 6) SE-SMR+PSA and indirect firing H2 combustion from the product stream recycle. The proposed process models with rigorous heat exchanger network design were simulated in Aspen Plus to understand the thermodynamic limitations in achieving the maximum CH4 conversion, H2 purity, CO2 capture efficiency, cold gas efficiency and net operating efficiency. A sensitivity study was also performed for changes in the reformer temperature, pressure, and steam to carbon (S/C) ratio to explore the optimal operating space for each case. The SE-SMR+PSA+H2 (Case 6) recycle process can achieve a maximum of 94.2% carbon capture with a trade-off in cold gas efficiency (51.3%), while a near 100% carbon capture with the maximum net efficiency of up to 76.3% is realisable by integrating CLC and PSA (Case 4) at 25 bar. Integration of oxy-fuel combustion lowered the net efficiency by 2.7% points due to the need for an air separation unit. In addition, the SE-SMR with the PSAOG process can be designed as a self-sustaining process without any additional fuel required to meet the process heat utility when the S/C ratio is ~3-3.5
Keywords: carbon capture; chemical-looping combustion; sorption enhanced steam methane reforming; Blue hydrogen production